Intra-stimulation discharges: An overlooked cortical electrographic entity triggered by direct electrical stimulation. Issue 5 (May 2015) - Karakis, Ioannis; Leeman-Markowski, Beth A.; Leveroni, Catherine L.; Kilbride, Ronan D.; Cash, Sydney S.; Eskandar, Emad N.; Simon, Mirela V.
Highlights Intra-stimulation discharges (IDs) can occur during language mapping and before after-discharges (ADs). High stimulus intensities, long stimulation durations, and presence of baseline epileptiform discharges at the stimulation site increase the probability of triggering IDs, and consequently, ADs. Attention to IDs may improve the safety and precision of neurophysiologic mapping.